2022
DOI: 10.24875/ciru.20001256
|View full text |Cite
|
Sign up to set email alerts
|

Aplicación de una calculadora de riesgo quirúrgico en una cohorte de pacientes de cirugía hepática en Veracruz, México

Abstract: Objetivo: Múltiples modelos han intentado predecir la morbilidad y mortalidad de las resecciones hepáticas (RH). Este estudio tiene por objetivo determinar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous studies have investigated the use of the online ACS NSQIP risk calculator for morbidity and mortality in patients undergoing hepatic and extrahepatic surgery. [7][8][9] These studies have demonstrated adequate performance of the model; however, further modifications were required to more accurately estimate outcomes. The online risk calculator used in these studies included several of the comorbidities analyzed in our model approach; however, what was unique to the current study was the utilization of pertinent preoperative laboratory values and a model that reduced the number of needed independent variables for prediction to 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated the use of the online ACS NSQIP risk calculator for morbidity and mortality in patients undergoing hepatic and extrahepatic surgery. [7][8][9] These studies have demonstrated adequate performance of the model; however, further modifications were required to more accurately estimate outcomes. The online risk calculator used in these studies included several of the comorbidities analyzed in our model approach; however, what was unique to the current study was the utilization of pertinent preoperative laboratory values and a model that reduced the number of needed independent variables for prediction to 9.…”
Section: Discussionmentioning
confidence: 99%
“…6 Previous studies have investigated the use of the online ACS NSQIP risk calculator for morbidity and mortality in patients undergoing hepatic and extrahepatic surgery. [7][8][9] These studies have demonstrated adequate performance of the model; however, further modifications were required to more accurately estimate outcomes. The objective of the current study was to develop a score-based risk calculator using a limited number of predictors to estimate mortality risk in patients undergoing hepatectomy.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%